Maturity and its assessment for admission into religious life with particular reference to institutes in Zimbabwe. - Maminimini, Helen Tendayi. (University of Ottawa (Canada), 2001)
Religious profession, by which certain Catholics publicly profess the three vows of poverty, chastity and obedience according to ecclesial law, is a juridic act. Consequently, professed members assume certain obligations and rights in the Church. The serious nature of the obligations of religious profession, obliges superiors of religious institutes to be vigilant in admitting into their institutes only those candidates who meet certain requirements. Canon 642 specifies some of these requirements. These are, the required age, health, suitable disposition and sufficient maturity to embrace the proper life of an institute. While it recommends the use of experts in determining the presence of these qualities, if necessary, the canon, also cautions superiors to respect individual privacy (c. 220) in the process. Apart from age which is easy to ascertain, each of the other listed requirements is so abstract, broad and difficult to define that the deliberate choice was made to simply focus our study on "sufficient maturity." The thesis attempts to define religious life and maturity and also explores methods of assessing the maturity required for admission in the novitiate of an institute. Even then, although maturity is mentioned several times in the Code, it is nowhere defined in clear terms seemingly because the law lacks the language and the tools to elaborate on its complex nature. As a result, an analytical inter-dialogue between theology, spirituality, canon law and psychology is used to bridge the gap between the legal requirements and the psychological concepts. The first chapter of the thesis presents a brief description of the essential elements of religious life, based on magisterial documents since the Second Vatican Council. It also defines personal maturity in its several aspects primarily from a psychological point of view. In order to reveal the relationship between the obligations of religious life and the personal maturity that is required for the life in its ideal state, chapter two examines in detail the role maturity plays in living out the three vows, common life and prayer life. In chapter three, the thesis analyses the methods currently used to assess the maturity of candidates admitted into religious life. The two main methods of psychological assessment identified in this study are psychological testing and behavioural assessment. Necessary measures to guard against unlawful violation of individual privacy of candidates during assessment are also discussed. The content of chapter four is centred on the applicability or suitability of the conclusions of our study to religious life in Zimbabwe.
Keywords: Religion, Clergy.